Penanaman modal asing dan demokrasi: analisis data panel Provinsi-Provinsi di Indonesia - Hazmi, Dolly; Ayu, Fitri; Kamarni, Neng (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
Foreign investment is very important for developing countries in economic development because of the low domestic investment capacity. Democracy is considered as one of the aspects that has an impact on investment, although there is still debate as to whether the impact is positive, negative, or neutral. Many other factors influence the inflow of foreign investment into a country, including the size of the economy, the level of wages, domestic investment, and the quality of human resources. Using a panel data regression analysis of provinces in Indonesia with a random effect model, we try to look at the factors that influence foreign investment inflows to Indonesia. We find that the democracy index in Indonesia's provinces does not affect foreign investment inflows Â